Memória, cultura e territorialidade no contexto da judicialização de conflitos: um olhar sobre a comunidade rural do Cajueiro, frente à expansão da cidade de São Luís/MA - LIMA NETO, Alexandre Moura (2021)
Traditional communities came to occupy a prominent place in discussions about memory, identity, culture and space. Therefore, the objective of this study was to analyze the observance of the preservation of the rights of the Cajueiro Community, as a result of the city's expansion in the context of conflicts, highlighting the socio-environmental and cultural ones. Considering that, from the implementation of Porto São Luís, having as interests the acquisition of capital by companies that exploit natural resources, problems emerged in the capital of Maranhão that extended to its historicity, memory and culture. It was thus instigated to understand the subjects who live in the Cashew Community, from the dynamics of its cultural preservation. It was essential to analyze the determining interests in the installation of the private port, in addition to evaluating the extent to which the preservation of the culture of Cajueiro Community was respected, considering the rationality in the legal proceedings arising from conflicts over the installation of the enterprise. Therefore, a relational research with a Bourdian profile was carried out with bibliographic and documental procedure, using as corpus three federal and state court proceedings arising from conflicts in the territorial area, the focus of the study. The research is also constituted by descriptive objectives, with a critical approach, being predominantly qualitative; we sought to deepen the understanding of the intersubjective variables that make up the social context researched, based on the theoretical framework of Foucault (2008), Canclini (1983; 1987), Marx and Engels (2010), Arcangeli (2018; 2020), Pedro (2017), Ferretti (2015), Santos (1988; 2002), Acselrad (2002; 2004; 2009; 2010), Bourdieu (1983; 1989; 2002; 2004; 2011), among others. With regard to the theoretical framework, the cultural rights of Cunha Filho (2000; 2004; 2008) and Cunha Filho, Botelho and Severino (2018) stand out; to discuss the judicialization of conflicts, the research by Souza Lima (2012) was used, and regarding the effectiveness and efficiency of the norm, Moreira (1984) and Barroso (1993; 2012), respectively. As a result of the research carried out, it was found that there are irregularities and illegalities in the granting of environmental licensing, which attests to a legal and administrative mechanism that is beneficial to the dominant system. The studies also pointed out that the Justice System, after the implementation of Porto São Luís, was unable to absorb and resolve all judicial conflicts in the Cajueiro Community area. Notwithstanding this, the existence of monocratic court decisions was observed that determined the stoppage of the works, which, if they were not carried out, would put at risk cultural aspects, memories and natural assets of the Cajueiro Community.